Sepsis-related cardiomyopathy: Not an easy task for ICU physicians - Zhang, Hongmin; Liu, Dawei (Journal of intensive medicine, 2022)
Sepsis-induced myocardial dysfunction is common. In addition to acute coronary syndrome, at least two types of left ventricular dysfunction can occur in septic patients: typical septic cardiomyopathy (SC) and sepsis-related takotsubo cardiomyopathy (ST). Although the definition of septic cardiomyopathy is based on left ventricular (LV) systolic dysfunction, both ventricles can be affected. In this context, it has been increasingly recognized that right ventricular (RV) systolic dysfunction is associated with long-term prognosis in septic patients. Unlike typical SC, ST patients usually displayed LV apical and circumferential mid-ventricular hypokinesia and basal hypercontractility. Timely and precise evaluation of heart dysfunction in sepsis patients is not easy but obviously mandatory. Further studies are still warranted regarding the mechanism, evaluation, and management of septic cardiomyopathy.